Business Model Canvas: Easy Peasy Tool / Nur Humaira Suhaimi - Suhaimi, Nur Humaira (2020)
Business Model Canvas (BMC) is a strategic management tool to quickly and easily define and communicate a business idea or concept. It can clearly show our business idea on a piece of paper that allows us to visualize the business model, detect weakness and target segment. It has 9 building blocks of the business model. It is a visual chart with elements describing a firm’s or product’s value proposition, customers, finances and sources. The BMC report for my product which is Easy Peasy tool can act as the business plan. It can helps me go run my business extensively in terms of market research, financial, target customers and target supplier. It may help in enhancing my business. Moreover, by using BMC I can see my business potential more clearly. In other words it can offer me an overview of the business idea from many perspectives, thus it makes us easier to produce Easy Peasy tool